Unleashing great teaching the secrets to the most effective teacher development - Weston, David 1979-; Clay, Bridget (London Routledge, 2018)
"This practical handbook takes the guesswork out of professional learning, showing school leaders how they can build a self-improving culture and remove barriers to learning.the authors set out their advice for how every school can bring in the best ideas from the whole system, and make sure that these have a lasting effect in the classroom. Packed full of examples, easy-to-use ideas and checklists, Unleashing Great Teaching brings together a vast body of experience gained by the Teacher Development Trust (UK), and shows how other schools can learn from these insights. From fostering a culture of evaluating impact to establishing good relationships, communication and a developmental culture, this book takes each and every aspect of the school system and reassesses its role as a driver of teacher and student success."--Provided by publisher.
1. Teacher learning: the building blocks -- 2. The purpose of professional learning: A framework of outcomes -- 3. Impact: Implementing and evaluating professional learning -- 4. Culture: The make or break for professional learning -- 5. Support and challenge: engaging effectively with experts -- 6. Planning professional learning across a whole year.
Includes bibliographical references.
Keywords: Effective teaching; Teachers -- Training of